2021
DOI: 10.3390/cells11010095
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Effects on NCC Are Attenuated during Inhibition of Cullin E3–Ubiquitin Ligases

Abstract: The thiazide-sensitive sodium chloride cotransporter (NCC) plays a vital role in maintaining sodium (Na+) and potassium (K+) homeostasis. NCC activity is modulated by with-no-lysine kinases 1 and 4 (WNK1 and WNK4), the abundance of which is controlled by the RING-type E3 ligase Cullin 3 (Cul3) and its substrate adapter Kelch-like protein 3. Dietary K+ intake has an inverse correlation with NCC activity, but the mechanism underlying this phenomenon remains to be fully elucidated. Here, we investigated the invol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…After determining that Nedd4-2 activity is important for modulating NCC abundance and degradation in MDCKI cells, we next tested if Nedd4-2 was important for lowering NCC abundance in response to high extracellular K + . As long-term effects on NCC are technically difficult to study in the inducible MDCKI-hNCC cell system, we switched to using ex vivo kidney tubule preparations ( Cheng et al, 2019 ; Kortenoeven et al, 2021 ; Murali et al, 2021 ; Poulsen et al, 2021 ) from mice lacking Nedd4-2 in the kidney tubule (referred to as Nedd4-2 KO) and relevant control mice. Tubules were incubated with different concentrations of K + (0.5, 3.5, and 8 mM) for 24 h and protein abundances were assessed using western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After determining that Nedd4-2 activity is important for modulating NCC abundance and degradation in MDCKI cells, we next tested if Nedd4-2 was important for lowering NCC abundance in response to high extracellular K + . As long-term effects on NCC are technically difficult to study in the inducible MDCKI-hNCC cell system, we switched to using ex vivo kidney tubule preparations ( Cheng et al, 2019 ; Kortenoeven et al, 2021 ; Murali et al, 2021 ; Poulsen et al, 2021 ) from mice lacking Nedd4-2 in the kidney tubule (referred to as Nedd4-2 KO) and relevant control mice. Tubules were incubated with different concentrations of K + (0.5, 3.5, and 8 mM) for 24 h and protein abundances were assessed using western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…The lower NCC phosphorylation following high dietary K + intake is due to reduced activity of the inwardly-rectifying potassium channels Kir4.1/Kir5.1 (a heterotetramer), changes in the basolateral plasma membrane potential, and reduced activity of the WNK-SPAK kinase signaling pathway ( Piala et al, 2014 ; Bazua-Valenti et al, 2015 ; Cuevas et al, 2017 ; Wu et al, 2019 ). Altered dietary K + also results in changes in activity of the Kelch-like protein 3 (KLHL3) and Cullin 3 (Cul3) E3 ubiquitin ligase complex that targets WNK kinases for degradation, altering NCC activity ( Ishizawa et al, 2016 ; Cheng et al, 2019 ; Kortenoeven et al, 2021 ; Murali et al, 2021 ; Poulsen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report showing an increase in cullin-1 expression in TALs from Sprague–Dawley rats when cullin neddylation is inhibited. However, this was not observed in homogenized whole kidney samples ( 80 ). Although the data suggest that cullin-1 is autoregulated, the data do not allow us to conclude that cullin-1 is responsible for mediating the cGMP-dependent increase in NKCC2 ubiquitination.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, Ishizawa et al ( 88 ) showed that a reduction in K + intake stimulates NCC phosphorylation while decreasing ubiquitination. On the other hand, Murali et al ( 80 ) showed that the increase in NCC ubiquitination due to high K + intake was attenuated when cullin activity was inhibited. Taken together, these studies suggest that an increase in cullin activation is indirectly related to NCC phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation